Arctic Biodiversity and Inuit Health - Knotsch, Cathleen; Lamouche, James (Université d'Ottawa | University of Ottawa, 2010)
In this publication, we show the link between environmental change, based on Inuit perspectives and direct observations, and biodiversity, which is the sum of all living beings and things. We summarize the many changes Inuit have reported as impacting biodiversity, such as the appearance of insects formerly not seen, and at the same time examine how local knowledge is crucial to adapting to changes in biodiversity. Finally, we discuss the connection between biodiversity and Inuit health and why changes in Arctic biodiversity will mean changes to human life in the Arctic. Inuit have been reporting environmental changes in the Arctic, such as differences in sea-ice thaw and freeze-up, for years and several publications have documented these observations from various regions of the circumpolar world. The most comprehensive approach to document these observations in Canada is found in the book Unikkaaqatigiit — Putting the Human Face on Climate Change: Perspectives from Inuit in Canada (Nickels et al., 2006). Unikkaaqatigiit summarizes what Inuit have said about environmental change. It is also one of the first published records of Inuit adaptations to climate change in that it reports on how communities and individuals are responding to change and adjusting to it in their daily lives. The main findings in our report rely upon published materials on biodiversity. The core of this report is based on materials produced under international and national biodiversity programs and documentation of Indigenous insights into climate change. The tables provide hands-on examples of how local observations can be organized to have relevance in discussions of biodiversity. Changes in climate and weather events in the Arctic and their subsequent effects on the biological systems of the region have impacts on food security and economic well-being of Inuit. Limited access to caribou, seal, fish, berries and other ‘country foods’ leads to greater reliance on imported store-bought foods. Aside from a change in diet, which can be stressful for the human body, the transition from nutrient- dense country foods to less nutritious store-bought foods may have an even more significant impact on the health of Inuit, in the short and long term. The link between the loss of biological diversity and the parallel loss of cultural diversity is only now beginning to be recognized. The Arctic is homeland to Inuit, not only in Canada but circumpolar, and Inuit are the first to see and feel the changes in ice, water and land. The pace of change has quickened and we can observe changes in temperature, plant growth and wildlife behavior within several calendar years instead of over centuries. Changes to the living resources of the Arctic translate into rapid changes in the lifestyles of local human populations and increased stress on the health and well-being of Inuit. We hope that this publication and others like it will draw attention to the importance of biodiversity in the circumpolar Arctic and that the world will be guided by the knowledge and wisdom of Inuit regarding the homelands, environment and biodiversity upon which they rely.
Keywords: environmental change; climate change; Inuit; food security; Traditional knowledge